TERAPI BERMAIN PUZZLE TERHADAP PENURUNAN TINGKAT KECEMASAN PADA ANAK USIA PRASEKOLAH (3-6 TAHUN) YANG MENJALANI KEMOTERAPI DI RUANG HEMATOLOGI ONKOLOGI ANAK - Fitriani, Winda; Santi, Eka; Rahmayanti, Devi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Anxiety was one of the psychological distress that can occur in children undergo chemotherapy.Puzzle is one of play form that allegedly could decrease anxiety levels in preschoolers. Thepurpose of this research was to know the effectiveness of puzzle play therapy on decreasinganxiety levels in preschoolers (3-6 years) undergo chemotherapy in Pediatric HematologyOncology RSUD Ulin Banjarmasin. This study was a pre-experimental study with One Grouppre-post test design. Sampling used consecutive sampling technique with 14 respondents. Theinstrument used an anxiety questionnaire of preschoolers that has been tested for validity andreliability. The result of research using wilcoxon sign rank test got p-value 0,005 showed thatpuzzle play therapy had an effect to decrease anxiety level in preschoolers undergo chemotherapyin Pediatric Hematology Oncology RSUD Ulin Banjarmasin. Play therapy using a puzzle can besuggested as one of the play therapy to decrease anxiety levels.